Optimization of Smart Policing and Democratic Policing Concepts as Polri's Efforts in Building Synergy with the Community to Realize Inclusive and Just Security Governance - Santoso, Joko Edy; Setiono, Joko; Gani, Yopik Gani (Jurnal Greenation Sosial dan Politik, 2025)
The security paradigm in the modern era has experienced a significant shift from a repressive approach to a more preventive, participatory, and technology-based model. In the Indonesian context, this is reflected in Polri’s efforts to adopt the Smart Policing and Democratic Policing concepts as a reform strategy for building inclusive and just security governance. Smart Policing emphasizes the use of information technology, big data, and artificial intelligence in detecting, analyzing, and preventing crime predictively. Meanwhile, Democratic Policing emphasizes the principles of transparency, accountability, respect for human rights, and community involvement in the security decision-making process. This study uses a normative legal method to analyze the legal basis and effectiveness of the implementation of police policies, referring to the latest regulations such as Law Number 2 of 2002 concerning the Police, Law Number 27 of 2022 concerning Personal Data Protection, and Police Regulation Number 8 of 2021 concerning Restorative Justice. The analysis shows that optimizing the two approaches still faces challenges in terms of limited digital infrastructure, regulatory gaps, and minimal independent civilian oversight. To realize a fair and democratic security system, it is necessary to strengthen institutional capacity, increase technological literacy for Polri personnel, and develop community participatory forums. The synergy between institutions and the public is key to building legitimacy and trust in the national security system.